Clinical impact of routine follow-up coronary angiography after second- or third-generation drug-eluting stent insertion in clinically stable patients - Choi, Seonghoon; Mun, Hee-Sun; Kang, Min-Kyung; Cho, Jung Rae; Han, Seong Woo; Lee, Namho (The Korean journal of internal medicine, 2015)
In the bare-metal stent era, routine follow-up coronary angiography (RFU CAG) was used to ensure stent patency. With the advent of drug-eluting stents (DESs) with better safety and efficacy profiles, RFU CAG has been performed less often. There are few data on the clinical impact of RFU CAG after second- or third-generation DES implantation in clinically stable patients with coronary artery disease; the aim of this study was to examine this issue. We analyzed clinical outcomes retrospectively of 259 patients who were event-free at 12-month after stent implantation and did not undergo RFU CAG (clinical follow-up group) and 364 patients who were event-free prior to RFU CAG (angiographic follow-up group). Baseline characteristics were compared between the groups. The Kaplan-Meier estimated total survival and major adverse cardiac event (MACE)-free survival did not differ between the groups (p = 0.100 and p = 0.461, respectively). The cumulative MACE rate was also not different between the groups (hazard ratio, 0.85; 95% confidence interval, 0.35 to 2.02). In the angiographic follow-up group, 8.8% revascularization was seen at RFU CAG. RFU CAG did not affect long-term clinical outcome after second- or third-generation DES implantation in clinically stable patients.